Perinatal outcomes of fetoscopic laser surgery for twin–twin transfusion syndrome in triplet pregnancy: cohort study, systematic review and meta‐analysis. (1st July 2022) - Mustafa, H. J.; Javinani, A.; Krispin, E.; Tadbiri, H.; Shamshirsaz, A. A.; Espinoza, J.; Nassr, A. A.; Donepudi, R.; Belfort, M. A.; Sanz Cortes, M.; Harman, C.; Turan, O. M.
ABSTRACT: Objectives: The aims of this study were to investigate the perinatal outcome of dichorionic triamniotic (DCTA) and monochorionic triamniotic (MCTA) triplet pregnancies complicated by twin–twin transfusion syndrome (TTTS) treated with fetoscopic laser photocoagulation (FLP) in two academic fetal centers, and to conduct a systematic review of previously published data to investigate perinatal survival in this targeted population. Methods: The first part of the study was a retrospective cohort study of prospectively collected data of consecutive triplet pregnancies with TTTS that underwent FLP at two fetal treatment centers between 2012 and 2020. Demographic, preoperative and operative variables and postoperative outcome were collected. Perinatal outcomes were investigated. The second part of the study was a systematic review and meta‐analysis of studies evaluating the outcome of DCTA and/or MCTA triplet pregnancies, including our cohort study. PubMed, Web of Science and Scopus were searched from inception to September 2020. Primary outcomes were fetal survival (survival to birth), neonatal survival (survival to 28 days of age) and gestational age (GA) at birth. Results: A total of 31 sets of triplets with TTTS managed with FLP were included in the cohort study. Of these, 24 were DCTA and seven were MCTA. There were no significant differences in preoperative and operative variables between the two groups. There were also no significant differences between groups in GA at delivery or perinatal survival rate, including fetal and neonatal survival of at least one triplet, at least two triplets and all three triplets. Nine studies, including our cohort study, were included in the systematic review (156 DCTA and 37 MCTA triplet pregnancies treated with FLP). The overall fetal and neonatal survival was 79% (95% CI, 75–83%) and 75% (95% CI, 71–79%), respectively, in DCTA cases and 74% (95% CI, 52–92%) and 71% (95% CI, 49–89%), respectively, in MCTA cases. The rate of preterm birth before 28 weeks and before 32 weeks' gestation was 14% (95% CI, 4–29%) and 61% (95% CI, 50–72%), respectively, in DCTA triplets and 21% (95% CI, 3–45%) and 82% (95% CI, 62–96%), respectively, in MCTA triplets. Conclusions: Triplet pregnancies with TTTS are at high risk of adverse perinatal outcome and preterm birth, regardless of chorionicity. The rate of survival after FLP in MCTA triplets was higher in our study than that reported in previous studies and is currently comparable with survival in DCTA triplets, which could be due to improved surgical skills. © 2022 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Resultados perinatales de la cirugía láser fetoscópica para el síndrome de transfusión feto‐fetal en el embarazo de trillizos: estudio de cohortes, revisión sistemática y metaanálisis Objetivos: Los objetivos de este estudio fueron investigar el resultado perinatal de los embarazos de trillizos dicoriónicos triamnióticos (DCTA, por sus siglas en inglés) y monocoriónicos triamnióticos (MCTA, por sus siglas en inglés) complicados por el síndrome de transfusión feto‐fetal (TTTS, por sus siglas en inglés) tratados con fotocoagulación láser fetoscópica (FLF) en dos centros fetales académicos, y realizar una revisión sistemática de los datos publicados previamente para investigar la supervivencia perinatal en esta población objetivo . Métodos: La primera parte del estudio fue un estudio de cohorte retrospectivo de datos recogidos prospectivamente de embarazos consecutivos de trillizos con TTTS que se sometieron a una FLF en dos centros de tratamiento fetal entre 2012 y 2020. Se recogieron variables demográficas, preoperatorias y operatorias, así como el resultado postoperatorio. Se investigaron los resultados perinatales. La segunda parte del estudio fue una revisión sistemática y un metaanálisis de los estudios que evaluaban el resultado de los embarazos de trillizos DCTA y/o MCTA, incluido el estudio de cohorte de la primera parte de este estudio. Se realizaron búsquedas en PubMed, Web of Science y Scopus desde el inicio hasta septiembre de 2020. Los resultados primarios fueron la supervivencia fetal (hasta el nacimiento), la supervivencia neonatal (hasta los 28 días de edad) y la edad gestacional (EG) al nacer . Resultados: En el estudio de cohorte se incluyeron 31 conjuntos de trillizos con TTTS tratados con FLF. De ellos, 24 eran DCTA y siete eran MCTA. No hubo diferencias significativas entre los dos grupos en las variables preoperatorias y operatorias. Tampoco hubo diferencias significativas entre los grupos en cuanto a la EG en el momento del parto o la tasa de supervivencia perinatal, incluida la supervivencia fetal y neonatal de al menos un trillizo, al menos dos trillizos y los tres trillizos. En la revisión sistemática se incluyeron nueve estudios, incluido el estudio de cohortes (156 embarazos de trillizos DCTA y 37 MCTA tratados con FLF). La supervivencia fetal y neonatal total fue del 79% (IC 95%, 75–83%) y del 75% (IC 95%, 71–79%), respectivamente, en los casos de DCTA y del 74% (IC 95%, 52–92%) y del 71% (IC 95%, 49–89%), respectivamente, en los casos de MCTA. La tasa de partos pretérmino antes de las 28 semanas y antes de las 32 semanas de gestación fue del 14% (IC 95%, 4–29%) y del 61% (IC 95%, 50–72%), respectivamente, en los trillizos DCTA y del 21% (IC 95%, 3–45%) y del 82% (IC 95%, 62–96%), respectivamente, en los trillizos MCTA . Conclusiones: Los embarazos de trillizos con TTTS tienen un alto riesgo de resultados perinatales adversos y de parto pretérmino, independientemente de la corionicidad. La tasa de supervivencia después de la FLF en los trillizos MCTA fue mayor en este estudio que la reportada en estudios anteriores y es comparable con la supervivencia en los trillizos DCTA, lo que podría deberse a una mejora en las destrezas quirúrgicas . 摘要: 胎儿镜激光手术治疗三胎妊娠的胎儿‐胎儿输血综合征围生期结局:队列研究、系统回顾和荟萃分析 目的: 本研究旨在评估在两家学术胎儿中心接受胎儿镜下激光凝固术(FLP)治疗的双绒毛膜双羊膜囊(DCTA)和单绒毛膜双羊膜囊(MCTA)三胎妊娠的胎儿‐胎儿输血综合征(TTTS)围生期结局，并对以前发表资料进行系统回顾，以揭示该目标人群的围生期存活情形。 方法: 本研究第一部分是对前瞻性收集的2012‐2020年期间两家学术胎儿中心接受FLP治疗的TTTS连续三胎妊娠资料进行回顾性队列研究。收集的资料包括人口统计学、术前和手术变量以及术后结局。针对围生期结局进行调查。本研究第二部分对DCTA和/或MCTA三胎妊娠结局的评估研究实施系统回顾和荟萃分析，包括我们的队列研究。我们检索从开业到2020年9月期间的PubMed、Web of Science和Scopus。主要结局包括胎儿存活率(存活至出生)、新生儿存活率(存活至28天)和出生时胎龄(GA)。 结果: 共计31例接受FLP治疗的TTTS三胎妊娠被纳入队列研究。 其中，24例为DCTA，7例为MCTA。术前和术中变量在两组之间无明显差异。各组的分娩时GA或围生期存活率也不存在显著差异，包括至少一个三胞胎、至少两个三胞胎和全部三个三胞胎的胎儿存活率和新生儿存活率。9项研究(包括我们的队列研究)被纳入系统回顾(接受FLP治疗的156例DCTA和37例MCTA三胎妊娠)。DCTA病例的总体胎儿存活率和新生儿存活率分别是79%(95% CI，75‐83%)和75%(95% CI，71‐79%)，MCTA病例则分别为74%(95% CI，52‐92%)和71%(95% CI，49‐89%)。DCTA三胎的28周前和32周前早产率分别是14%(95% CI，4‐29%)和61%(95% CI，50‐72%)，MCTA三胎则分别是21%(95% CI，3‐45%)和82%(95% CI，62‐96%)。 结论: 发生TTTS的三胎妊娠围生期结局和早产风险非常高，与绒毛膜数无关。 在本研究中，MCTA三胎接受FLP治疗存活率高于以往研究报告结果，目前与DCTA三胎存活率相当，原因可能是 手术技能提升。